Pengaruh Likuiditas, Profitabilitas, Aktivitas, Leverage, dan Kepemilikan Institusional Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Retno Sari; Wuri Septi Handayani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research was conducted aiming to determinethe effect of liquidity, profitability, activity, leverage and institutional ownership on company value Empirical Study of Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) with a research periode of 2019-2023. The sampling technique in this study used purposive sampling with a sample of 52 companies. The data analysis used in this research is multiple linear regression analysis using a statistical test tool, namely SPSS version 22. Based on the research results, the results indicate that liquidity, profitability, activity, and institutional ownership have a positive significant effect on firm value, while institutional ownership have a negative significant effect on firm value